Genetic-archaeological evidences about the origin of common bean in Brazil - Freitas, Fábio de Oliveira (Pesquisa Agropecuaria Brasileira, 2006)
This work discusses the origin of common bean, Phaseolus vulgaris L. Modern and archaeological samples were genetically analyzed, using sequences of phaseolin (Phs). The archaeological sample was found in a cave in northern Minas Gerais State. Our results showed that this sample is close to those found in Northern South America and Mexico, indicating cultural influences in the past, between those regions and Minas Gerais. Besides, there must have been a single domestication event, probably between Northern South America and Mexico.
Keywords: Phaseolus vulgaris; evolution; phaseolin; human migration; domestication; allele networks